Effects of acute exercise, dehydration and rehydration on cognitive function in well-trained athletes - Irwin, C.; Campagnolo, N.; Iudakhina, E.; Cox, G. R.; Desbrow, B. (Journal of Sports Sciences, 2018)
This study investigated the effects of aerobic exercise, fluid loss and rehydration on cognitive performance in well-trained athletes. Ten endurance-trained males (25 ± 5 years; 175 ± 5 cm; 70.35 ± 5.46 kg; VO2max, 62.95 ± 7.20 ml · kg.min-1) lost ~2.5 ± 0.6% body mass via continuous cycling exercise at ~65% peak sustainable power output (60 min duration) before consuming different beverages (Water = W1 and W2, Sustagen Sport = SS, Powerade = PD) and food ad libitum on four separate occasions. Cognitive function using a four-choice reaction time task (CRT), body mass, fluid consumption volumes, urine samples and subjective ratings (alertness, concentration, energy) were obtained before and after exercise, and hourly during recovery (for 4 h). CRT latency was significantly reduced immediately after exercise compared to pre-exercise measures for all trials (W1 = -16 ± 18 ms, W2 = -22 ± 21 ms, PD = -22 ± 22 ms, SS = -19 ± 26 ms). However, this effect was short-lived with subsequent measures not different from pre-exercise values. No difference in CRT accuracy was observed at any time across all trials. Subjective ratings were not different at any time across all trials. Aerobic exercise, hypohydration or an interaction between these two may provide a small cognitive performance benefit. However, these effects are temporary and confined to the immediate post-exercise period.